Determinants Associated with School Discipline in Schools of Tuwaiq Educational Office (Riyadh) for the Year 2025: A Descriptive-Analytical Study of Students' Perceptions - Al-Shehri, Dhafer Saed; Al-Qayawi, Manal Abdullah; Musawi, Hassan Hussein; Al-Uraini, Amaal Sulaiman (Journal of Educational and Psychological Sciences, 2025)
This study aimed to identify factors affecting school discipline from students' perspectives at schools under the Tuwaiq Educational Office in Riyadh in 2025, examine differences based on gender and educational stage, and explore the relationships between these factors. A descriptive-analytical method was utilized, employing a questionnaire distributed to a sample of 823 students. Findings indicated that the most influential factors on school discipline were positive student-teacher relationships, followed by adopting the "school as a community" approach and students' psychological well-being. Moreover, no significant differences were found related to gender or educational stage for most factors. The study emphasizes the importance of strengthening positive student-teacher relationships and promoting a supportive school environment that enhances students' psychological health. This research addresses a gap in the local literature by exploring students' perceptions of school discipline in the Saudi context. The study also recommends future research to investigate the impact of social-emotional learning programs on school discipline across various educational stages and to develop and evaluate an integrated intervention model based on the factors identified in the current research.
Keywords: school discipline; school approach as a community; positive reinforcement; social interaction; emotional learning; academic stress